Aerobic exercise training ameliorates craving and inhibitory control in methamphetamine dependencies: A randomized controlled trial and event-related potential study. (May 2017) - Wang, Dongshi; Zhu, Ting; Zhou, Chenglin; Chang, Yu-Kai
Abstract: Objective: Methamphetamine (MA) usage has been recognized as a prominent substance-abuse issue. While exercise training reportedly improves fitness and mental status in the MA-dependent, how exercise training affects addiction and cognitive deficiency has yet to be established. The current study aimed to determine the effects of aerobic exercise training on both MA-associated cravings and inhibitory control among those with MA dependencies. Design: A 12-week randomized controlled trial. Method: Sixty-two people with MA dependencies recruited through the Drug Rehabilitation Bureau were assigned to either an aerobic exercise or attentional control group, with 50 participants completing the trial. The aerobic exercise program involved three 30-min sessions of moderate-intensity exercise per week. Along with a pre-test assessment, craving levels were evaluated every three weeks, and data on neutral and MA-related inhibitory control as well as its elicited neuroelectric activation were collected at the end of the intervention. Results: Compared with the control group, the exercise group experienced attenuated MA craving levels after 6 weeks of the exercise program, and the decreased trend was maintained until the termination of treatment. In the post-test, the exercise group also demonstrated more accuracy in behavioral inhibitory control as well as greater N2 amplitude in the Nogo condition of both the standard and MA-related tasks than those in the control group or pre-test. Conclusions: The current study provides the first evidence that aerobic exercise training may be efficacious for MA-associated cravings and inhibitory control from behavioral and neuroelectric perspectives among MA-dependent individuals. Highlights: Whether exercise training affects methamphetamine (MA)-associated addiction and inhibitory control has yet to be determined. A moderate-intensity aerobic exercise program with three 30-min sessions per week for 12 weeks attenuated MA craving. Aerobic exercise may lead to better inhibitory control and greater N2 amplitude in tasks with higher inhibition demand.